Transition metal-free phosphonocarboxylation of alkenes with carbon dioxide via visible-light photoredox catalysis - Qiang Fu (Nature Portfolio, 2019)
Phosphonyl and carboxyl groups are valuable functional groups, however their simultaneous incorporation via catalytic difunctionalization of alkenes has not been realized yet. Here the authors report the phosphonocarboxylation of alkenes with CO2 via visible-light photoredox catalysis.